Energy depletion of embryos and yolk-sac feeding larvae of the liparid snailfish Careproctus pallidus (Vaillant 1888) - Bruno, Daniel Osvaldo; Rojo, Javier Hernán; Boy, Claudia Clementina (Polar Biology)
The snailfish, Careproctus pallidus, is a liparid fish that spawns within the branchial chambers of the king crab Lithodes santolla and develops its embryonic stages inside the chambers until it forms a well-developed free-living yolk-sac feeding larvae hatch. The aim of this work was to explore the decrease in energy content of C. pallidus during its early development. Five egg masses with embryos in cleavage stage were extracted from the branchial chambers of five different king crabs and kept in aquaria through hatching until complete absorption of the yolk-sac. To monitor energy content during development, subsamples of eggs (in cleavage, tail-bud, and late embryo stages) and larvae [1, 13, 20–22 and 24–26 days post-hatch (DPH)] were removed. Each stage of development (eggs and larvae) was weighed (wet weight), counted (N) and dried at 60°C. Both energy density (ED) and energy content (EC) per individual (egg or larva) were measured. Significant differences in ED and ECi were observed among the early stages of C. pallidus, although pairwise comparisons differed. From the earliest developmental stage (cleavage) to a larva of 24–26 DPH, the ED of C. pallidus decreased by approximately 40% and the ECi by 87%. Compared with other marine fish species, C. pallidus seems to begin life with lower energy if size of egg, incubation period, and degree of development until it reached the hatching stage are considered. Thus, the energy allocation during the early development of this liparid fish with a particular reproductive strategy is discussed. Fil: Bruno, Daniel Osvaldo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Rojo, Javier Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Boy, Claudia Clementina. ...